Neuroprotective and nootropic activity of Clitorea ternatea Linn.(Fabaceae) leaves on diabetes induced cognitive decline in experimental animals - Karuna A Talpate; Uma A Bhosale; Mandar R Zambare; Rahul S Somani (Wolters Kluwer Medknow Publications, 2014)
Purpose: Ethanol extract of Clitorea ternatea (EECT) was evaluated in diabetes-induced cognitive decline rat model for its nootropic and neuroprotective activity. Materials and Methods: Effect on spatial working memory, spatial reference memory and spatial working-reference memory was evaluated by Y maze, Morris water maze and Radial arm maze respectively. Neuroprotective effects of EECT was studied by assaying acetylcholinesterase, lipid peroxide, superoxide dismutase (SOD), total nitric oxide (NO), catalase (CAT) and glutathione (GSH) levels in the brain of diabetic rats. Results: The EECT (200 and 400 mg/kg) was found to cause significant increase in spatial working memory ( P < 0.05), spatial reference memory ( P < 0.001) and spatial working-reference ( P < 0.001) in retention trials on Y maze, Morris water maze and Radial arm maze respectively. Whereas significant decrease in acetylcholinesterase activity ( P < 0.05), lipid peroxide ( P < 0.001), total NO ( P < 0.001) and significant increase in SOD, CAT and GSH levels was observed in animals treated with EECT (200 and 400 mg/kg) compared to diabetic control group. Conclusions: The present data indicates that Clitorea ternatea tenders protection against diabetes induced cognitive decline and merits the need for further studies to elucidate its mode of action.